2011
DOI: 10.1097/01.ccm.0000408627.24229.88
|View full text |Cite
|
Sign up to set email alerts
|

1: Activation of Poly(adp-Ribose) Polymerase-1 Contributes to Nad+ Depletion and Impaired Nad+ Dependent Mitochondrial Respiration Following Status Epilepticus

Abstract: of open aneurysm repair (OAR). The fact that survival from treatment has not changed, however, has little to do with declining incidence and mortality from AAA in the popula 4,5 Screening programs need periodic reassessment. It is time to reassess this one.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 0 publications
0
35
0
Order By: Relevance
“…Instead, drawing on a prior study—by one of the coauthors [20] —and on recently reported research literature that showed the evidence for disproportionate time allocation, we evaluated whether structured tools had any effect on moderating the effects of disproportionate time allocation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Instead, drawing on a prior study—by one of the coauthors [20] —and on recently reported research literature that showed the evidence for disproportionate time allocation, we evaluated whether structured tools had any effect on moderating the effects of disproportionate time allocation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Cohen et al [18] examined video-recordings of 23 end-of-week handoff sessions in a 21-bed intensive care unit (ICU) and found that patients discussed earlier received about 50% more time than the patients discussed later in the same session, regardless of their severity or complexity of illness. Similarly, Kannampallil et al, [20] reported an average decrease of 54 seconds for every additional patient discussion during morning rounds in a Cardiothoracic ICU. As a part of a larger clinical trial, Sung et al [21] analyzed 759 patient discussions from 2 clinical teams and found similar decrease in the time spent for patients discussed later during the rounds, after adjusting for illness severity.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Patients achieve target balance within 500 ml on fewer than half of therapy days, and manual charting of ultrafiltration volumes contains inaccuracies on 60% of therapy days [35]. Accurate and meticulous volume and fluid management is crucial in AKI, as hypervolemia is associated with increased mortality [36,37].…”
Section: Leveraging Data Capture In Dialysis To Improve Patient Carementioning
confidence: 99%
“…For patients, this can regard delayed potentially beneficial therapeutic decisions, the maintenance of aggressive therapy and the resultant lower quality of treatment. Almoosa et al [20] have shown that lack of clear decisions concerning the continuation or withdrawal of treatment, as well as waiting for admission, prolonged unjustified ICU stays and the prevented hospitalisation of other patients. The negative impact of conflicts on the ICU team manifests as lack of coherence, lower efficiency and quality of work, and irrational behaviour.…”
mentioning
confidence: 99%